Identification of Molecular Mechanism of OSA with Hypertension Based on Multiple Microarray Analysis. (4th July 2022) - Zhang, Xizhu; Jing, Gang; Qi, Liqing; Ma, Mingzhu; Li, Liting; Shen, Ningning; Guo, Zheng; Gao, Xiaoling
Abstract : Purpose . OSA is closely associated with hypertension, and both epidemiological and experimental studies have confirmed that OSA is one of the most important independent risk factors for hypertension. The pathological mechanisms by which OSA causes hypertension are not well understood, and in this paper, we explored the molecular mechanisms by which OSA may mediate hypertension at the bioinformatics level. Materials and Methods . We downloaded disease-related datasets from the GEO public database, calculated the differential genes between the two groups of patients by the limma package, and then further constructed the WGCNA network based on the clinical characteristics of patients to explore the important regulatory genes in the disease. Subsequently, ssGSEA was used to explore the potential molecular mechanisms of disease progression and GSVA was applied to analyze the specific signaling pathways. Finally, we performed real-time quantitative PCR (qRT-PCR) to validate these pivotal genes. Results . Three genes were selected as target genes, namely, GPR179, RNF150, and JPH4. The results showed they were strongly correlated with immune cell content that high expression of the three core genes was associated with myogenesis, angiogenesis, oxidation, metabolism, and PI3K/AKT/mTOR pathways. qRT-PCR validated that all three genes have statistically significant differences between the OSA group and OSA combined with hypertension group. Conclusion . Our study provides new evidence for the potential molecular mechanisms of OSA combined with hypertensive disease as well as diagnosis and treatment.